2001
DOI: 10.1515/jpem.2001.14.3.257
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ovarian Structure and Hyperandrogenism in Premature Pubarche

Abstract: The aim of this study was to describe the ovarian structure (OS) and its relationship with hyperandrogenism in girls with premature pubarche (PP). A pelvic ultrasound was carried out in 23 girls with PP and in 57 prepubertal age-matched controls (C), and the OS was subdivided into five classes (c): 1-homogeneous; 2-microcystic, 3-multicystic, 4-polycystic and 5-follicular. In the girls with PP, an ACTH test was performed, and the presence of hormonal levels >3 SD of postpubertal normal levels and not compatibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2001
2001
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
4
0
3
Order By: Relevance
“…Ibänez et al, 8 found that pubertal girls with a history of PP showed exaggerated ovarian androgen VOLUME synthesis throughout puberty. In more recent studies, we have described a generalized adrenocortical hyper-responsiveness in girls with PP, which is more accentuated in girls with microcystic ovaries than in those with homogeneous ovaries 14 . The hyper-responsiveness of steroids to adrenocorticotropic hormone (ACTH) has been described previously in women with polycystic ovarian syndrome (PCOS) 9 .…”
Section: Introductionmentioning
confidence: 90%
“…Ibänez et al, 8 found that pubertal girls with a history of PP showed exaggerated ovarian androgen VOLUME synthesis throughout puberty. In more recent studies, we have described a generalized adrenocortical hyper-responsiveness in girls with PP, which is more accentuated in girls with microcystic ovaries than in those with homogeneous ovaries 14 . The hyper-responsiveness of steroids to adrenocorticotropic hormone (ACTH) has been described previously in women with polycystic ovarian syndrome (PCOS) 9 .…”
Section: Introductionmentioning
confidence: 90%
“…Por sua vez, as meninas com PP parecem apresentar hiperinsulinismo e uma relação de jejum da insulina/glicose (FIGR -Fasting Insulin to Glucose Ratio) sugestiva de RI desde antes da puberdade, quando a PP é diagnosticada, e através de todos os estádios do desenvolvimento puberal (12,22,23). Em estudo prévio, demonstramos que o hiperandrogenismo adrenal pode não ter um efeito adverso sobre a sensibilidade à insulina (SI) na infância, contudo a presença de obesidade, acanthosis nigricans e da FIGR sugestiva de RI são relativamente comuns em meninas com PP (22).…”
Section: Discussionunclassified
“…Esta associação entre PP e SOP tem sido descrita mesmo em pacientes não-obesas e parece estar relacionada ao grau de hiperandrogenismo. Em estudos prévios, descrevemos que meninas com PP e ovários microcísticos eram menos obesas do que as com ovários homogêneos, embora com um maior grau de hiperandrogenismo e níveis mais elevados de IGFBP-3, que tem sido considerado como fator preditivo negativo da sensibilidade à insulina durante a puberdade (31,32). Geralmente a evolução para a SOP ocorre durante o desenvolvimento puberal, principalmente naquelas meninas com predisposição genética.…”
Section: Obesidade E Baixo Peso Ao Nascer Na Pubarca Precoceunclassified